An alternative continuous form of Arya and Paris model to predict the soil water retention curve of a soil. (August 2021) - Campos-Guereta, Ivan; Dawson, Andrew; Thom, Nicholas
Highlights: A new model, ACAP, has been developed, based based on Arya and Paris, 1981, but overcoming some previous detected problems. A simple physic-empirical continuous expression is reached to estimate the water retention curve of a soil. The resulting expression use of one only parameter β, for a selected scaling parameter D0. The inputs for the new expression are basic soil properties: the grain size distribution and porosity. Abstract: Arya and Paris developed a model in 1981 to predict the water retention curve of a soil from the grain size distribution and the porosity. This model was very convenient due to the simplicity of the input parameters, and because experimental measures are expensive and with no lack of uncertainties. The model was based on very simple equations but the need to discretize the grain size distribution restricted its usability. A new model is presented, preserving the physical meaning but solving this dependency and other issues and allowing a continuous expression that was not possible with the original model. The new model is very convenient and practical as expressions are easy to implement, and its predictions depend on only one parameter for which some recommended values are also included. Limitations and uncertainties of the model are also discussed. Graphical abstract: Image, graphical abstract